How remote sensing can track adaptation to climate change, from the farm to the global level - CGIAR (CGIAR System Organization, 2023)
Researchers at the Alliance of Bioversity-CIAT and the University of Galway have developed a method to track agricultural adaptation to climate change from the global to the farm level using satellite remote sensing. The “Biomass Climate Adaptation Index” overcomes challenges that until now have prevented progress assessment of climate change goals and will enable more responsive investments and interventions to build climate-resilient food systems.